(untitled) (Вестник транспорта - Transport xabarnomasi, 2025)
Railway automation and telemechanics systems widely rely on control units based on electromagnetic relays. Despite their long-term effectiveness, the physical wear of these relays, increasing maintenance costs, and signal transmission delays have highlighted the need for modern control methods. The limited lifespan of electromagnetic relays and the necessity for continuous maintenance significantly impact operational efficiency. This study focuses on enhancing the microprocessor-based control unit for single-aspect maneuver signals by replacing traditional electromagnetic relay systems with modern Programmable Logic Controllers (PLCs). PLC-based control systems offer several advantages, including faster processing speeds, real-time diagnostics, remote monitoring, and seamless network integration, leading to increased reliability and cost-effectiveness. The research investigates how PLC controllers improve system reliability, reduce maintenance costs, and optimize railway signaling operations. By enabling real-time monitoring, diagnostics, and automated control, this approach ensures higher adaptability and efficiency in railway automation. The findings contribute to the modernization of railway signaling systems and provide recommendations for practical implementation.